3 Answers | Add Yours
Use the point-slope equation:
`y - y_1 = m(x - x_1)`
We're given x = 3, y = -6, and m = -4/3. Let's plug them into the point-slop equation:
`y - -6 = -4/3(x - 3)`
We then simplify:
`y + 6 = -4/3 x + 4`
We then solve for y to obtain our solution:
`y = -4/3x - 2`
The point slope formula is `y-y' = m(x-x')` where m is the slope and x' and y' are the values of one of the points.
To find the slope you need to know the rise (change in the value of y) and the value of the run (the change in the value of x). The slope is rise / run. y changed from -6 to 3 or a change of +9. x changed from 3 to -4 or a change of -7.
`(Delta y)/(Delta x)` = `(+9)/-7` = `(rise)/(run)` = slope = m
Using this value for m and the point 3, -6 we get-
` `` `` <strong>y-(-6) = -9/7(x-3)</strong> `` `` `
` ` `y+6 = -9/7x+9/7*3`
`y = -9/7`x -2 1/7
Test: Use the other point y=3 and x=-4
`3 = -9/7(-4) - 2 1/7`
`3 = 36/7 - 15/7` = 21/7 = 3 The equation works.
i think it's 3x+-6=14
We’ve answered 330,385 questions. We can answer yours, too.Ask a question